Analogies Used in a General Biology Course: How is DNA Conserved Across Generations? - Nazlı Rüya Taşkın Bedizel; Nursen Azizoğlu (Journal of Science Learning, 2023)
The present study has two main goals. First, it aims to examine the analogies an instructor uses about "DNA conservation across generations" in a university-level General Biology course. Second, it aims to examine the analogies used in those lessons according to Thiele and Treagust's framework. A qualitative case study design is adopted in the present study to investigate the cases in depth. Data were collected from an instructor with 35 years of teaching and research experience during a general biology course. According to the results, the instructor used many analogies, but seven of them were about to explain DNA conservation across generations. These analogies were analyzed by quoting the instructor and using figures and the classification mentioned above framework. It was noted that most of the analogies used by the instructor about DNA are structural-functional, verbal-pictorial, concrete, enriched, and embedded activators. For students to learn abstract concepts such as DNA correctly, this study provides examples of analogies that have been tried with well-established similarity relationships between source and target that engage students in the lesson. The effectiveness of the analogies on students' achievement and problem-solving skills can be tested in future studies.